Utilization of Subnetworks through Distributed Gateway in Lan Environment - Ahmad Basri Hashim; Roshidi Din; Md Zahir Mat Cha; Azmi Md Saman (International Journal of Management Studies, 2004)
It is a globally accepted fact that there is a significant increase in the use of Internet in a local area network (LAN) environment. Whilst the reliance (dependence) on the costly, and d z ~ c u l to maintain, hardware and software brings about problems for organizations with small budget, the full utilization of networks is questionable, for example, at schools and colleges where server failure consistently occurs that leads toward inability to access the Internet. To address issues relating to this matter, this paper discusses on the viable alternative of IP masquerading that allows the interconnection of sub networks and distribution of gateways in a multiple internal LAN environment. For the server which acts as a gateway to the Internet, an IP masquerading distribution based on Linux is used. A distributed gateway based on alternative routes to other gateways in deferent sub networks will minimize disconnections. The situation will ensure reliable and continuous connection through alternative sub networks in the event of a connection failure in adjoining sub-network. This results in a reliable and cheaper LAN-Internet connection through the IP masquerading servers as an alternative to proxy server software. It also ensures reliable and continuous Internet connection through an alternative sub network in the event of a connection failure in an adjoining sub network.